Qualidade da silagem de Cynodon cv. Jiggs com diferentes níveis de inclusão de farelo de canola - De Col, Dionathan Divã (2017)
The aim will be to evaluate the quality of Jiggs silage (Cynodon spp.) with different levels of canola meal inclusion. The Jiggs grass is established in private property, with a total area of 11 ha, of which 2.3 ha are destined for pasture and of these, 1.8 ha is formed of Cynodon cv.Jiggs.. To evaluate the quality of silage will be taken 5 treatments: 0; 6; 12; 18 and 28% inclusion of canola meal in the total dry matter of the jiggs, With 6 replicates each treatment, the material will be cut to 5cm of the ground, crushed and ensiled in PVC microsilos, 200g of dry sand in lab oven will be placed in the bottom of the each to evaluate losses of humidity. The analyzed variables will be pH, buffer power, losses by effluent and gas, ammonia, NDF, FDA, CP, MM, DM, soluble carbohydrate and in vitro digestibility. The results obtained for pH and buffer capacity underwent linear growth as the inclusion levels increased, since the loss by effluents had the opposite effect reducing linearly as the addition of the levels, the loss by gases had a quadratic effect. The variables MS, PB, soluble carbohydrate and "in vitro" digestibility obtained linear growth with the addition of canola meal, values for OM increased with the inclusion of the meal as well as the levels of MM decreased. The NDF contents had a quadratic effect with a small decrease, whereas the values for FDA had a linear effect, decreasing with the increase of the inclusion of canola meal.